KERAGAAN TANAMAN BAWANG MERAH (ALLIUM ASCALONICUM L.) PADA BERBAGAI DOSIS PUPUK KCL DI LAHAN RAWA LEBAK - Muhammad Yasin; Lelya Pramudyani; Aidi Noor; Retna Qomariah (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Performances of Shallot Plant (Allium Ascalonicum L.) In Various Dosage of KCl Fertilizer In Swampy Land. Swampy land utilization for vegetable crops is a strategic choice for developing agriculture because swampy land has great potential and prospect as a national food source to offset the shrinking of productive land on the island of Java which is converted to the development of non-agricultural sectors. However, the utilization of swampy land requires proper cultivation techniques such as site-specific fertilization including the application of potassium that is an essential nutrient for shallots. Adequate application of potassium fertilizer in plants known can improve crop resistance to pests, increase yields (seeds or tubers), and also improve tuber quality. The aims of this study was to get the dose of KCL fertilizer which provided the highest weight of shallot tubers. The study was conducted in June 2016 - November 2016 in Hulu Sungai Tengah District, South Kalimantan with the type of swampy land, using the Biru Lancor variety and Randomized Block Design with 8 replications. Parameters observed were the percentage of grew plants, wet weight per tuber, number of tubers, diameter of tubers and production. The results showed the use of KCL fertilizer at a dose of 300 kg ha-1 produced the highest yields and dry weight of shallots. Pemanfaatan lahan rawa lebak untuk tanaman sayuran merupakan pilihan yang strategis karena lahan rawa lebak mempunyai potensi dan prospek besar sebagai sumber pangan nasional untuk mengimbangi penciutan lahan produktif di pulau Jawa yang dialihfungsikan untuk pembangunan sektor non pertanian. Namun pemanfaatan lahan rawa lebak memerlukan teknik budidaya yang tepat seperti pemupukan spesifik lokasi termasuk pemberian kalium yang merupakan hara penting bagi bawang merah. Pemberian pupuk kalium yang cukup pada tanaman telah diketahui dapat meningkatkan ketahanan tanaman terhadap hama penyakit, hasil panen (biji atau umbi), dan juga memperbaiki kualitas umbi. Penelitian ini bertujuan untuk mendapatkan dosis pupuk KCL yang memberikan bobot umbi bawang merah paling tinggi. Penelitian dilaksanakan pada bulan Juni 2016 – Nopember 2016 di Kabupaten Hulu Sungai Tengah, Kalimantan Selatan dengan tipe lahan rawa lebak, menggunakan varietas Biru Lancor dan Rancangan Acak Kelompok dengan ulangan 8 kali. Parameter yang diamati meliputi persentase tanaman yang tumbuh, bobot basah per umbi, jumlah umbi, diameter umbi, dan produksi. Hasil menunjukkan penggunaan pupuk KCL dengan dosis 300 kg ha-1 di menghasilkan produksi dan bobot kering bawang merah paling tinggi.